2021
DOI: 10.1186/s12886-021-01885-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and complications following one-way air-fluid exchange technique for vitreous hemorrhage post vitrectomy in proliferative diabetic retinopathy patients

Abstract: Background To evaluate the efficacy and outcomes of one-way surgical technique for the treatment of vitreous hemorrhage post vitrectomy on proliferative diabetic retinopathy (PDR) patients. Methods This retrospective case series include 47 PDR patients who had vitrectomy with balanced saline solution tamponade and have developed vitreous hemorrhage without significant absorption. The one-way air-fluid exchange procedure which involves the applicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…A third study found that the use of BSS tamponade after vitrectomy for PDR was associated with good visual outcomes and a low rate of complications [10].…”
Section: Exploring Factors Influencing Erm Development Following Vitr...mentioning
confidence: 98%
“…A third study found that the use of BSS tamponade after vitrectomy for PDR was associated with good visual outcomes and a low rate of complications [10].…”
Section: Exploring Factors Influencing Erm Development Following Vitr...mentioning
confidence: 98%
“…Vitreus içine hava tampolanması, sklerotomilerde sızdırmazlığı sağlamada, göz içi basınç oluşturmada, vitre içi hemorajilerde erken dönem ameliyat sonrası kanama oluşmasını engellemede ve hava-sıvı değişimi manevrasında kullanılmaktadır. 12,13 Optikon vitrektomi sisteminde steril hava önceden ayarlanmış bir değerde verilerek göz basıncının otomatik kontrolü sağlanır. Hava dağıtım modülü 5-80 mmHg aralığında ayarlanabilir olarak tasarlanmıştır.…”
Section: Hava Tamponlanmasıunclassified
“…[1–5] These patients may also suffer from vitreous hemorrhage and tractional retinal detachment that can lead to severe visual loss or blindness. [6–8] In the patients without intervention, approximately half of them will experience profound visual loss in 5 years. [9,10]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These patients may also suffer from vitreous hemorrhage and tractional retinal detachment that can lead to severe visual loss or blindness. [6][7][8] In the patients without intervention, approximately half of them will experience profound visual loss in 5 years. [9,10] As the standard treatment of proliferative diabetic retinopathy for more than 4 decades, panretinal photocoagulation is able to cause regression of retinal neovascularization and reduce the risk of severe vision loss for proliferative diabetic retinopathy by destroying areas of peripheral retina to reduce the neovascularization formation but preserving central vision.…”
Section: Introductionmentioning
confidence: 99%